The Theoretical-Conceptual Model of Churning in Human Resources: The Importance of Its Operationalization - Pirrolas, Olga Alexandra Chinita; Correia, Pedro Miguel Alves Ribeiro (Sustainability, 2021)
Given the current socio-economic context in which the labor market is set in, if we were to consider both employment opportunities in specific economic periods and the individual expectations workers have regarding one’s working conditions, it should be a matter of one’s individual right of choice to decide whether or not to stay or leave and change companies. The paper we present before you took into account the phenomenon of churning as a cyclical process. Our main goal was to understand the main causes leading to it in the context of human resources and, ultimately, what were the consequences emerging from it. In order to carry out this analysis, we put forward a conceptual-theoretical model of the phenomenon of churning, made possible through the analysis of both the currently available literature and the empirical studies and conclusions stemming from the latter. The aforementioned analysis allowed us to trace all main causes responsible for the origin of churning and also, to understand how it could be implemented further on, in order to minimize the costs associated with hiring new personnel and retaining qualified employees by resorting beforehand to the implementation of strategic measures of human resources retention. By applying the methodology based on grounded theory, this study allowed us to further contribute to the already available, yet limited, literature and definition of this multifaceted and greatly complex subject that is the phenomenon of churning.